Prevalence of anaphylaxis and prescription rates of epinephrine auto-injectors in urban and rural areas of Korea - Cho, Hyunseok (Korean J Intern Med, 2019)
BACKGROUND/AIMS: Despite the clinical importance anaphylaxis and the recent increase in its occurrence, studies regarding the epidemiology of anaphylaxis, risk factors for anaphylaxis, and epinephrine auto-injector (EAI) prescription status for patients with anaphylaxis remain poorly described. Thus, we investigated the prevalence of anaphylaxis and prescription rates of EAI in urban and rural areas in Korea. METHODS: We used data from the 2010 to 2014 Health Insurance Review and Assessment database. Anaphylaxis was identified through physician-certified diagnoses using the International Classification of Diseases 10th (ICD-10) codes (T780, T782, T805, T886). Data on prescription rates of EAI were collected from the Korea Orphan & Essential Drug Center, the only pharmacy exclusively dealing with EAI in Korea. The prescription rates of EAI were defined as the number of EAI prescribed against the number of patients with anaphylaxis. RESULTS: The prevalence of anaphylaxis over the 5-year period was 0.023%. The annual prevalence of anaphylaxis increased over the 5-year period. Anaphylaxis was more common in males than in females (54% vs. 46%) and in the population aged 50 to 59 years old. For regional analysis, urban areas showed a relatively lower prevalence of anaphylaxis (17.3 per 100,000 individuals) along with higher prescription rates (12.0%) of EAI for patients with anaphylaxis. In contrast, rural areas showed a relatively higher prevalence of anaphylaxis (28.8 per 100,000 individuals) along with lower prescription rates (3.1%) of EAI. CONCLUSIONS: The prevalence of anaphylaxis has increased annually in Korea. There were regional differences in the prevalence of anaphylaxis and prescription rates of EAI between urban and rural areas in Korea.